2000
DOI: 10.1053/jhep.2000.8700
|View full text |Cite
|
Sign up to set email alerts
|

Iron reduction as an adjuvant to interferon therapy in patients with chronic hepatitis C who have previously not responded to interferon: A multicenter, prospective, randomized, controlled trial

Abstract: Hepatic iron concentration has consistently been observed as being directly correlated with the response to interferon therapy in chronic hepatitis C virus (HCV). We therefore conducted a randomized, controlled trial comparing iron reduction by phlebotomy with iron reduction followed by retreatment with interferon in 96 patients with chronic hepatitis C who had previously not responded to a course of interferon. During the initial phase when all patients were undergoing phlebotomy, we found that serum alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
94
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 22 publications
10
94
0
2
Order By: Relevance
“…Neither group achieved significant improvements in terms of cure of CHC, but both showed evidence of histological improvements, with less severe hepatic inflammation (22). These favorable effects of iron reduction alone confirmed and extended earlier reports showing significant improvements in serum ALT levels in patients with CHC who previously had not responded to interferon when they underwent iron reduction by therapeutic venesection (23,24).…”
Section: Iron and Viral Hepatitissupporting
confidence: 82%
“…Neither group achieved significant improvements in terms of cure of CHC, but both showed evidence of histological improvements, with less severe hepatic inflammation (22). These favorable effects of iron reduction alone confirmed and extended earlier reports showing significant improvements in serum ALT levels in patients with CHC who previously had not responded to interferon when they underwent iron reduction by therapeutic venesection (23,24).…”
Section: Iron and Viral Hepatitissupporting
confidence: 82%
“…The lack of a correlation between HIC and response of patients with hepatitis C to antiviral treatment agrees with the majority of the results regarding phlebotomy as coadjuvant treatment 7,10,19 . DI BISCEGLIE et al 10 showed that in patients with hepatitis C not responding to interferon monotherapy iron depletion by phlebotomy did not result in a higher SVR rate during retreatment, despite an association with improved liver injury manifested by a decrease in transaminases and improved liver histopathology after phlebotomy.…”
supporting
confidence: 87%
“…DI BISCEGLIE et al 10 showed that in patients with hepatitis C not responding to interferon monotherapy iron depletion by phlebotomy did not result in a higher SVR rate during retreatment, despite an association with improved liver injury manifested by a decrease in transaminases and improved liver histopathology after phlebotomy. Similarly, in the study of HERRERA 19 iron depletion by phlebotomy did not improve SVR in the retreatment of patients who were previously non-responders.…”
mentioning
confidence: 99%
“…Increased iron indices have also been associated with poor response to treatment with interferon-␣ (9 -12). In other studies, however, hepatic iron concentration did not influence the response to interferon-␣ treatment (13,14), and phlebotomy did not substantially improve the efficacy of antiviral therapies (15,16).…”
mentioning
confidence: 82%